APPLICATION OF LOAD BALANCING ALGORITHMS FOR IMPROVING THE QUALITY OF SERVICE - Joldasbayev, С.К; Kulambayev, Б.О (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
To develop solutions to the problems of providing high-speed Internet, that is, a high-quality service, up to a certain point, there is the possibility of improving quality by increasing the hardware resources of the system, but, as practice shows, quantity does not always mean quality, and the effectiveness of the service delivery system takes into account the advantageous positioning of resources with algorithmic load balancing on servers with maximum benefit, both for the user and for the party providing services. This article provides the results of research and analysis of balancing algorithms, implementation methods for load balancing on servers and improving the quality of service delivery. Research in this direction is very relevant and in demand, the article provides an analysis and description of static and dynamic solutions, the advantages and disadvantages of algorithms.